Socio-ecological research on children’s quality of life in Bryansk region - Moskalenko O.P.; Kovaleva E.L. (Научно-технический вестник Брянского государственного университета)
Quality of life evaluation was validated and applied according to the results of the survey of children’s and teenagers’ quality of life assessment index. The connection between the impact of anthropogenic factors and children’s and teenagers’ health complex index was detected.